Prevention of vertical transmission in the “Syphilis No!” Project: a study on the specificities of the investigation committees/space in the North Region of Brazil - Mareco, Thereza Cristina de Souza; Lima, Thaísa Gois Farias de Moura Santos; Santos, Marquiony Marques dos; Horta, Ana Paula Cruz Beja Orrico (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Committees for investigation of vertical transmission (CIVTs) are strategic for the prevention of vertical transmission of syphilis (PVTS) and represent one of the fundamental actions of the project “Syphilis No!”. This is mainly because of their role in the analysis of opportunities that were missed by the network of surveillance and care, and their potential to identify failures/difficulties in responding to syphilis and because they are configured as a space for recommending intervention to qualify the health service network. Objective: To describe and analyze a situation of CIVT/syphilis investigation spaces as strategic for PVTS from the implementation of the Syphilis No! project in priority municipalities in the North region of Brazil. Methods: Exploratory-descriptive study, with a qualitative case study approach. The data collection was carried out online, using the necessary questionnaires through the project at Plataforma LUES/FormLUES, from July 2019 to December 2020, and reports, minutes of meetings and reports of experiences, among other documents registered by project actors. Content analysis and bibliographic/documentary review were used. Results: The North region has eight priority municipalities for Syphilis No!, all with some CIVT strategy for syphilis. After the project implementation, five priority municipalities and three states in the region started to rely on CIVTs in their initial training for PVTS. Among the difficulties in the establishment and strengthening of CIVTs was the lack of human resources. Strategic actors and players in the North region pointed out advances/improvements in the service network since the committees’ establishment, such as organization of the investigative space, an investigation by home visit/medical records, and expansion of the network. As for the missed opportunities in PVTS, we found a relationship between absences/failures in access to adequate prenatal care. Conclusion: CIVT strategies are important spaces in PVTS, and their maintenance as a prevention axis in the Syphilis No! project is essential for the reduction of congenital syphilis and, consequently, infant mortality.